Pengaruh Pengungkapan Sustainability Report, Audit Tenure, Capital Intensity dan Profitabilitas terhadap Nilai Perusahaan - Mariah Ulfa; Harti Budi Yanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of Sustainability Report disclosure, audit tenure, capital intensity, and profitability on firm value. The objects of this study were consumer cyclical and consumer non-cyclical companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The sample was obtained using a purposive sampling technique, resulting in 214 observations. Data analysis was performed using a random effects model and processed using E-Views software. The test results indicate that Sustainability Report disclosure and capital intensity have no effect on firm value. Meanwhile, audit tenure has a negative effect on firm value, indicating that the longer the auditor's tenure, the lower the firm value. Conversely, profitability has a positive effect on firm value, meaning that the higher the company's ability to generate profits, the higher the firm value. These findings have implications for management and investors in considering factors that influence firm value.